The Relationship Between Islamic Fundamentalism and Radicalism With Social Conflict - Irawan, Deni; Arifin, Zarul (AL-TAHRIR, 2021)
Abstract: Islamic fundamentalism has often been accused as a source of conflict so that it should be ended immediately. And the radical movement should put forward a complete understanding of diverse religions. Likewise, in every movement, it is necessary to keep the political and economic interests away from religion, because such factors triggers inter-religious conflict. The brutal act by a group of people who claims the most righteous by displaying the most sinister and frightening face of Islam, is really far from Islamic values. Islam is rahmatan lil â€˜alamin, especially towards fellow Muslims who believe in the truth of Islam based on the Koran and the Sunnah as the main and first source of Islamic teachings. If this motto is implemented seriously, the conflicts that have occurred will not be repeated. In its further development, fundamentalism undergoes a change, a shift, and is further away from its origin. The discussion of fundamentalism today is more associated with a negative impression that Islam is a religion of violence, anti-progress and establishment, conservative, antiWestern, and always takes violence to achieve its goals. This labeling and stigmatization of course has greatly marginalized Islam in international relations. This kind of stigmatization can be understood by Muslims so that they also hold counters in various ways, including counter discourse. However, the efforts made by Muslims have not been able to change the world view of Islam, especially the Western world. Islam to this day is still perceived as a violent religion.Â Ø§Ù…Ù„Ù„Ø®Øµ: ÙƒØ§Ù… ÙŠØªÙ… Ø§Ù„ØªØ¹Ø¨Ø±ÙŠ Ø¹Ù†Ù‡Ø§ ÙŠÙ ÙƒØ«Ø±ÙŠ Ù…Ù† Ø§Ø£Ù„ØÙŠØ§Ù† ÙŠÙ Ø´ÙƒÙ„ Ø§ØªÙ‡Ø§Ù…Ø§Øª ØŒ Ø¨Ø£Ù† Ø§Ø£Ù„ØµÙˆÙ„ÙŠØ© Ø§Ø¥Ù„Ø³Ø§Ù„Ù…ÙŠØ© Ù…ØµØ¯Ø± Ù„Ù„Ø±ØµØ§Ø¹ ÙˆÙŠØ¬Ø¨ Ø¥Ù†Ù‡Ø§Ø¤Ù‡Ø§ Ø¹Ù‰Ù„ Ø§Ù„ÙÙˆØ±. ÙˆÙŠØ¬Ø¨ Ø£Ù† ØªØ¹Ø²Ø² ØØ±ÙƒØ© Ø§Ù„Ø±Ø§Ø¯ÙŠÙƒØ§Ù„ÙŠØ© Ø§Ù„ÙÙ‡Ù… Ø§Ù„ÙƒØ§Ù…Ù„ Ù…Ù„Ø®ØªÙ„Ù Ø§Ø£Ù„Ø¯ÙŠØ§Ù†. ÙˆØ¨Ø§Ù…Ù„Ø«Ù„ ÙŠÙ ÙƒÙ„ ØØ±ÙƒØ© ØŒ ÙŠØ¬Ø¨ Ø¥Ø¨Ø¹Ø§Ø¯ Ø§Ù…Ù„ØØªÙˆÙ‰ Ø§Ù„Ø³ÙŠØ§ÙŠØ³ ÙˆØ§Ø§Ù„Ù‚ØªØµØ§Ø¯ÙŠ Ø¹Ù† Ø§Ù„ØªÙ†ÙˆØ¹ ØŒ Ø£Ù„Ù† Ù‡Ø°Ø§ Ø¹Ø§Ù…Ù„ ÙŠØ«Ø±ÙŠ Ø§Ù„Ø±ØµØ§Ø¹ Ø¨Ø§Ø³Ù… Ø§Ù„Ø¯ÙŠÙ†. Ø¥Ù† Ø§Ù„Ø¹Ù…Ù„ Ø§Ù„ÙˆØÙŠØ´ Ù…Ù„Ø¬Ù…ÙˆØ¹Ø© Ù…Ù† Ø§Ø£Ù„Ø´Ø®Ø§Øµ Ø§Ù„Ø°ÙŠÙ† ÙŠØ´Ø¹Ø±ÙˆÙ† Ø¨Ø§Ø£Ù„Ù…Ø§Ù† ÙˆÙŠØ´Ø¹Ø±ÙˆÙ† Ø¨Ø§Ù„ØµØ§Ù„Ø Ù…Ù† Ø®Ø§Ù„Ù„ Ø¥Ø¸Ù‡Ø§Ø± Ø§Ù„ÙˆØ¬Ù‡ Ø§Ø£Ù„ÙƒØ±Ø« Ø±Ø´Ø§Ù‹ ÙˆØ®ÙˆÙØ§Ù‹ Ù„Ø¥Ù„Ø³Ø§Ù„Ù… Ø¨Ø¹ÙŠØ¯ ÙƒÙ„ Ø§Ù„Ø¨Ø¹Ø¯ Ø¹Ù† Ø§Ù„Ù‚ÙŠÙ… Ø§Ø¥Ù„Ø³Ø§Ù„Ù…ÙŠØ©. Ø§Ø¥Ù„Ø³Ø§Ù„Ù… Ù‡Ùˆ Ø±ØÙ…Ø© Ù„Ø£Ù„Ù…Ù†ÙŠ ØŒ ÙˆØ®Ø§ØµØ© ØªØ¬Ø§Ù‡ Ø¥Ø®ÙˆØ§Ù†Ù‡Ù… Ø§Ù…Ù„Ø³Ù„Ù…Ù†ÙŠ Ø§Ù„Ø°ÙŠÙ† ÙŠØ¤Ù…Ù†ÙˆÙ† Ø¨ØÙ‚ÙŠÙ‚Ø© Ø§Ø¥Ù„Ø³Ø§Ù„Ù… Ø¹Ù‰Ù„ Ø£Ø³Ø§Ø³ Ø§Ù„Ù‚Ø±Ø¢Ù† ÙˆØ§Ù„Ø³Ù†Ø© Ø¨Ø§Ø¹ØªØ¨Ø§Ø±Ù‡Ø§ Ø§Ù…Ù„ØµØ¯Ø± Ø§Ù„Ø±Ø¦ÙŠÙŠØ³ ÙˆØ§Ø£Ù„ÙˆÙ„ Ù„Ù„ØªØ¹Ø§Ù„ÙŠÙ… Ø§Ø¥Ù„Ø³Ø§Ù„Ù…ÙŠØ©. Ø¥Ø°Ø§ ØªÙ… Ø·Ø±Ø Ù‡Ø°Ø§ ØŒ ÙÙ„Ù† ØªØªÙƒØ±Ø± Ø§Ù„Ù†Ø²Ø§Ø¹Ø§Øª Ø§Ù„ØªÙŠ ØØ¯Ø«Øª. ÙŠÙ Ø§Ù„ØªØ·ÙˆØ±Ø§Øª Ø§Ù„Ø§Ù„ØÙ‚Ø© ØŒ Ø´Ù‡Ø¯Øª Ø§Ø£Ù„ØµÙˆÙ„ÙŠØ© ØªØºÙŠØ±ÙŠØ§Øª ÙˆØªØÙˆØ§Ù„Øª ÙˆØ£Ø¨Ø¹Ø¯Øª Ø¹Ù† Ø£ØµÙ„Ù‡Ø§. Ø¥Ù† Ù…Ù†Ø§Ù‚Ø´Ø© Ø§Ø£Ù„ØµÙˆÙ„ÙŠØ© ÙŠÙ Ø§Ù„ÙˆÙ‚Øª Ø§Ù„ØØ§ÙŠÙ„ Ù…Ø±ØªØ¨Ø·Ø© Ø£ÙƒØ±Ø« Ø¨Ø§Ø¥Ù„Ø³Ø§Ù„Ù… Ø¨Ø§Ù†Ø·Ø¨Ø§Ø¹ Ø³Ù„Ø¨ÙŠ Ø¨Ø£Ù† Ø§Ø¥Ù„Ø³Ø§Ù„Ù… Ø¯ÙŠÙ† Ø¹Ù†ÙŠÙ ÙˆÙ…Ø¹Ø§Ø¯ Ù„Ù„ØªÙ‚Ø¯Ù… ÙˆÙ…Ø¤Ø³Ø³ ÙˆÙ…ØØ§ÙØ¸ ÙˆÙ…Ø¹Ø§Ø¯ Ù„Ù„ØºØ±Ø¨ ÙˆÙŠØªØ®Ø° Ø§Ù„Ø¹Ù†Ù Ø¯Ø§Ù…Ø¦Ù‹Ø§ Ù„ØªØÙ‚ÙŠÙ‚ Ø£Ù‡Ø¯Ø§ÙÙ‡. ÙˆØ¨Ø§Ù„Ø·Ø¨Ø¹ ÙØ¥Ù† Ù‡Ø°Ø§ Ù‹ Ø§Ù„ØªÙˆØ³ÙŠÙ… ÙˆØ§Ù„ÙˆØµÙ… ÙŠÙ‡Ù…Ø´ Ø§Ø¥Ù„Ø³Ø§Ù„Ù… ØÙ‚Ø§ ÙŠÙ Ø§Ù„Ø¹Ø§Ù„Ù‚Ø§Øª Ø§Ù„Ø¯ÙˆÙ„ÙŠØ©. Ù…ÙŠÙƒÙ† Ù„Ù„Ù…Ø³Ù„Ù…Ù†ÙŠ Ø£Ù† ÙŠÙÙ‡Ù…ÙˆØ§ ÙˆÙŠÙÙ‡Ù…ÙˆØ§ Ù‡Ø°Ø§ Ø§Ù„Ù†ÙˆØ¹ Ù…Ù† Ø§Ù„ÙˆØµÙ… ØØªÙ‰ ÙŠØªØµØ¯ÙˆØ§ Ù„Ù‡Ø§ Ø¨Ø·Ø±Ù‚ Ù…Ø®ØªÙ„ÙØ© ØŒ Ù…Ø¨Ø§ ÙŠÙ Ø°Ù„Ùƒ Ø§Ù„Ø®Ø·Ø§Ø¨ Ø§Ù…Ù„Ø¶Ø§Ø¯. Ø¥Ø§Ù„ Ø£Ù† Ø§Ù„Ø¬Ù‡ÙˆØ¯ Ø§Ù„ØªÙŠ ÙŠØ¨Ø°Ù„Ù‡Ø§ Ø§Ù…Ù„Ø³Ù„Ù…ÙˆÙ† Ù…Ù„ ØªÙƒÙ† Ù‚Ø§Ø¯Ø±Ø© Ø¹Ù‰Ù„ ØªØºÙŠØ±ÙŠ Ù†Ø¸Ø±Ø© Ø§Ù„Ø¹Ø§Ù…Ù„ Ø§Ø¥Ù„Ø³Ø§Ù„Ù…ÙŠ ØŒ ÙˆØ®Ø§ØµØ© ÙÙ†Ø¸Ø± Ø¥Ù‰Ù„ Ø§Ø¥Ù„Ø³Ø§Ù„Ù… Ø¹Ù‰Ù„ Ø£Ù†Ù‡ Ø¯ÙŠÙ† Ø¹Ù†Ù. Ø§Ù„Ø¹Ø§Ù…Ù„ Ø§Ù„ØºØ±ÙŠØ¨. ØØªÙ‰ Ø§Ø¢Ù„Ù† ØŒ Ø§Ù„ ÙŠØ²Ø§Ù„ ÙŠAbstrak: Seperti yang sering diungkapkan dalam bentuk tudingan, bahwa fundamentalisme Islam merupakan sumber konflik sehingga harus segera diakhiri. Dan gerakan radikalisme harus mengedepankan pemahaman yang utuh tentang beragam agama. Begitu pula dalam setiap gerakan, muatan politik dan ekonomi perlu dijauhkan dari keberagaman, karena inilah faktor yang memicu terjadinya konflik yang mengatasnamakan agama. Tindakan brutal sekelompok orang yang merasa paling aman dan merasa paling benar dengan menampilkan wajah Islam yang paling seram dan menakutkan, sungguh jauh dari nilai-nilai Islam. Islam adalah rahmatan lil â€˜alamin, terutama terhadap sesama umat Islam yang meyakini kebenaran Islam berdasarkan Alquran dan Sunnah sebagai sumber utama dan pertama ajaran Islam. Jika ini dikedepankan maka konflik yang telah terjadi tidak akan terulang kembali. Dalam perkembangan selanjutnya, fundamentalisme mengalami perubahan, pergeseran, dan semakin jauh dari asalnya. Pembahasan fundamentalisme saat ini lebih banyak dikaitkan dengan Islam dengan kesan negatif bahwa Islam adalah agama yang kekerasan, anti kemajuan dan kemapanan, konservatif, anti Barat, dan selalu mengambil kekerasan untuk mencapai tujuannya. Pelabelan dan stigmatisasi ini tentu saja sangat memarjinalkan Islam dalam hubungan internasional. Stigmatisasi semacam ini dapat dipahami dan dipahami oleh umat Islam sehingga mereka pun mengadakan tandingan dengan berbagai cara, termasuk tandingan wacana. Namun upaya yang dilakukan oleh umat Islam belum mampu mengubah pandangan dunia Islam, khususnya dunia Barat. Islam hingga saat ini masih dipersepsikan sebagai agama kekerasan.